Genetic Differentiation in Isolated Primate Groups (Zoological Archives: An International Journal, 2023)
Habitat fragmentation -- the division of continuous forest into smaller, increasingly isolated patches by agriculture, roads, and urban expansion -- is the primary driver of primate population decline globally, affecting 65% of primate species across tropical and subtropical biomes. Genetic consequences of fragmentation are compounding the demographic impacts: small isolated populations accumulate inbreeding and lose adaptive variation through genetic drift, while gene flow cessation prevents the genetic rescue that could otherwise sustain demographic viability. This study presents the most comprehensive multi-species, multi-site conservation genetics analysis of habitat-fragmented primate populations yet conducted, genotyping 1,847 individuals from 84 populations of 18 primate species at 24 microsatellite loci and 8,470 SNPs, integrated with landscape resistance modelling and a 10-year demographic dataset. Population genetic differentiation increased significantly with fragment isolation (FST vs. least-cost path distance: r = 0.74; p < 0.001) and was significantly higher in fragments < 100 ha than in continuous forest populations (mean FST 0.184 vs. 0.047; t = 18.4; p < 0.001). Effective population size (Ne) declined below 50 in 34.7% of sampled fragments -- the IUCN minimum threshold for short-term genetic viability. Genetic rescue potential (assessed by admixture modelling) was significant in 14 of 18 species, with gene flow restoration via forest corridor planting predicted to increase Ne by 2.84-fold within 10 years under the most optimistic landscape restoration scenario.